(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2018)
The present study aimed to measure how verbal (instructions) and nonverbal (pictures) contexts exert control over verbal responses in a total verbal episode. Participants consisted in five undergraduate students. The procedure was divided in three phases: in the first phase the context “orange” was manipulated; in the second phase the context “point”; and, in the third phase the context “tennis”. All phases had three experimental situations (SE). In SE-1, SE-4, and SE-7 only the verbal context was manipulated. In SE-2, SE-3, SE-5, SE6, SE-8, and SE-9 the verbal and nonverbal contexts were manipulated. For each SE, the participants were required to submit written answers. Data analysis was made using subjects as their own control (withinsubjects design) and comparison between participants (between-subject design). Possible response classes were previously established, and all written answers were classified in agreement or disagreement with the context, either with the discriminative stimulus (Sd) or with none of the established classes. It was found that the different contexts controlled the meaning of words in the written behavior.